When management myths collide? : case study of management control systems in two Norwegian companies, operating in Russia - Svishchev, Roman (Universitetet i Nordland, 2011)
Masteroppgave i bedriftsøkonomi - Universitetet i Nordland, 2011 In this case study I have described two companies: Norwegian-Russian joint venture Rossnor and Reinertsen NWR, founded as a foreign direct investment of a parent company. I have analyzed management control systems of both companies with focus on challenges, arising in cross-cultural settings. This research indentifies and questions differences in myths of Russian and Norwegian management and shows how they can be resolved through the use of management control. Pursuing the goal of establishing links between different types of myths, challenges for managers and design of management control system a model of process relationship has been developed. The contribution of this model is that it emphasizes the necessity of two types of organizational learning as tools for reconsidering beliefs and assumptions of managers and redesigning management control systems, based on changes and new myths, with purpose to handle new challenges. Case of Rossnor proved that double-loop learning is critical for joint ventures and should supplement single-loop learning.